The Effect of the PhET Simulation Media-based PjBL Learning Model on Improving Learning Outcomes - Yuan Oemar Surindani; Dinn Wahyudin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2026)
This study aims to examine the effect of the Project-Based Learning (PjBL) model, integrated with PhET Interactive Simulations, on improving the science learning outcomes of fifth-grade elementary school students in magnetism, electricity, and technology in everyday life. A quasi-experimental design with a pretest-posttest control group was employed, involving 60 fifth-grade students from SDN 21 Sijuk, divided into an experimental class (n=30) receiving PjBL-PhET instruction and a control class (n=30) receiving conventional instruction. Data were collected through a validated 23-item multiple-choice test (KR-20 = 0.82), a structured observation sheet for student activities (Cohen's κ = 0.85), and a student response questionnaire (Cronbach's α = 0.91). Results showed that the experimental class achieved a significantly higher mean posttest score (85.67) than the control class (73.33), with a higher N-Gain of 0.71 compared to 0.25 in the control group. An independent sample t-test confirmed a statistically significant difference (p = 0.000) with a large effect size (Cohen's d = 1.70). Student learning activities in the experimental class achieved an average engagement of 87.5% (very active), with engagement gradually increasing across meetings. Student responses toward the learning approach were highly positive (89.3%), particularly regarding its benefits for conceptual understanding (91.0%). These findings demonstrate that integrating PjBL with PhET simulations enhances cognitive learning outcomes, active participation, and affective responses in elementary science education.